Regional socio-environmental characteristics associated with inadequate prenatal care during pregnancy: an ecological study of 47 prefectures in Japan - Eri Osawa; Tomoko Kodama (BMC, 2021)
Abstract Background Prenatal care (PNC) is a crucial health service that reduces the potential risks of adverse pregnancy and childbirth outcomes. It is monitored as one of the indicators of Universal Health Coverage (UHC) under the United Nations' Sustainable Development Goals. However, there are still mothers who do not use PNC, even when UHC has been achieved. As there have been few reports on the impact of local socio-environmental characteristics within the country, this study aimed to examine the association between local socio-environmental factors and inadequate use of PNC in Japan. Methods We conducted an ecological analysis of 47 prefectures in Japan using public open data. The dependent variables were the inadequate use of PNC, which are the rates of pregnant women who missed visiting PNC until 28 weeks' gestational age (GA) or those who never attended PNC before childbirth, and the independent variables were prefectural data of socio-economic, educational, and healthcare workforce-related factors. Multiple logistic regression analysis was used to examine the associations. Results The rate of pregnant women with late PNC initiation and never attending PNC before childbirth was 3.00-11.24 and 0.23-8.06 per 1000 pregnant women, respectively. Population numbers and densities, divorce rates, percentages of non-Japanese nationalities, and low percentages of high school enrolment were positively associated with inadequate PNC use. There was no statistically significant association with healthcare workforce, such as the number of obstetricians and gynaecologists. Conclusions This ecological study revealed that inadequate PNC use is more common in urban areas with more non-Japanese nationality and lower education enrolment. There may be a need to provide education for those who do not have access to reproductive health education, such as that offered in high schools. Further studies are required to examine factors that affect access to PNC in Japan.